1997
DOI: 10.1124/mol.52.4.667
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8-Tetrachlorodibenzo-p-dioxin-Induced Activation of a Protein Tyrosine Kinase, pp60src, in Murine Hepatic Cytosol Using a Cell-Free System

Abstract: SUMMARY 2,3,7, was found to activate protein kinases under cell-and nucleus-free conditions in isolated C57 mouse liver cytosol (100,000 ϫ g supernatant). This action of TCDD was found to be aryl hydrocarbon receptor (AHR) dependent, concentration dependent, and inhibited by genistein, a tyrosine kinase inhibitor. The lowest concentration of TCDD to produce a statistically significant increase in protein phosphorylation was 10 pM. We also investigated the possibility that a protein kinase is physically associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 39 publications
1
26
1
2
Order By: Relevance
“…Based on these findings, this model warrants further investigation. The results presented here suggest that Tetrahymena thermophila responds differently when exposed to different types of environmental hormones, and that these responses are similar to those observed in some multicellular organisms [31][32][33][34][35][41][42][43]. Furthermore, interaction network analysis of the exposure to TCDD provided rich information suggesting that T. thermophila would be a good unicellular, eukaryotic model for investigation of molecular mechanisms triggered by exposure to toxicants at the whole-genome level.…”
Section: Network Analysis Of Tcdd In T Thermophilamentioning
confidence: 74%
See 2 more Smart Citations
“…Based on these findings, this model warrants further investigation. The results presented here suggest that Tetrahymena thermophila responds differently when exposed to different types of environmental hormones, and that these responses are similar to those observed in some multicellular organisms [31][32][33][34][35][41][42][43]. Furthermore, interaction network analysis of the exposure to TCDD provided rich information suggesting that T. thermophila would be a good unicellular, eukaryotic model for investigation of molecular mechanisms triggered by exposure to toxicants at the whole-genome level.…”
Section: Network Analysis Of Tcdd In T Thermophilamentioning
confidence: 74%
“…Accordingly, microarray analysis of exposure of Tetrahymena to the toxicants suggested that the functions of the differentially expressed genes varied among toxicant-treated sets. These functions coincided with the characteristics of the toxicants, and some of them have been reported in multicellular organisms [31][32][33][34][35][41][42][43]. Thus, T. thermophila has the potential to be a unicellular model for toxic research because it can reflect general patterns of biological responses to these toxicants that match those of other eukaryotic organisms.…”
Section: Identification Of Differentially Expressed Genes and Categormentioning
confidence: 99%
See 1 more Smart Citation
“…In rodent adipose and liver tissues, it was reported that Src may be associated with components of the cytosolic AhR complex (5,12). To determine whether AhR and Src are present in the same protein complex in colon epithelial cells, we performed coimmunoprecipitation experiments.…”
Section: Tcdd-induced Cell Proliferation Is Mediated By Transactivatimentioning
confidence: 99%
“…One of the tyrosine kinases that is related to the action of AhR, c-Src, is known to be activated by TCDD in vivo [25][26][27] and in vitro, 28) but it is not clear how c-Src is activated or whether its activity is needed for the activation of AhR. Tyrphostin B48 is known to be a specific inhibitor of the tyrosine kinase activity of the epidermal growth factor receptor (EGFR), and the EGFR is one of the target molecules that is inhibited by genistein.…”
Section: Discussionmentioning
confidence: 99%